(untitled) (Scientific journal of the Fergana State University, 2023)
This article highlights the history of the early official diplomatic relations of the Bukhara Khanate with Russia. In the article, based on local sources and a number of works by Russian ambassadors, military men and researchers, it is substantiated that the main factor in the relationship between these two states is trade, economic and political relations.